A coefficient is a number before a variable. For example, in 2x, the 2 would be the coefficient
Well, isn't that a happy little math problem! To find out what 2x plus 2 equals, you simply need to add 2 to whatever number x represents. It's like adding a couple of friendly little birds to your painting to make it even more beautiful!
To find the product of x squared and 2x squared, you multiply the coefficients (2 and 1) to get 2, and then add the exponents of x (2 and 2) to get x to the power of 4. Therefore, x squared times 2x squared is equal to 2x^4.
In mathematics, an equation is a mathematical formula that expresses the equality of two expressions, by connecting them with the equals sign =. Example: 2x + 3 = 7 In this equation, 2x + 3 becomes included as one expression, and 7 is another expression. This equation declares that the two expressions need to be identical. To solve the equation for x, you'd do following steps: Subtract 3 from both sides of the equation the equation: 2x + 3 - 3 = 7 - 3 2x = 4 Divide both sides by 2: 2x/2 = 4/2 x = 2 Therefore, the solution to 2x + 3 = 7 is x = 2.
Oh, dude, you're hitting me with some math lingo here. So, like, the quotient of 300 and the quantity of x times 2 is just 150 divided by x. It's like dividing 300 by 2x, but simpler. Math can be fun, right?
0
If that was 2x^2 + 5x + 2, it would factor to (2x + 1)(x + 2)
4x^2 - ox - 25 = 4x^2 - 25 which is a difference of two squares (DOTS)= (2x)^2 - (5)^2So, the factorisation is (2x + 5)*(2x - 5).4x^2 - ox - 25 = 4x^2 - 25 which is a difference of two squares (DOTS)= (2x)^2 - (5)^2So, the factorisation is (2x + 5)*(2x - 5).4x^2 - ox - 25 = 4x^2 - 25 which is a difference of two squares (DOTS)= (2x)^2 - (5)^2So, the factorisation is (2x + 5)*(2x - 5).4x^2 - ox - 25 = 4x^2 - 25 which is a difference of two squares (DOTS)= (2x)^2 - (5)^2So, the factorisation is (2x + 5)*(2x - 5).
e 2x = (1/2) e 2x + C ============
The additive inverse is x5 + 2x - 2.
(12x3 + 14x2 + 14x + 2)/(4x + 2) simplify= (6x3 + 7x2 + 7x + 1)/(2x + 1)1. 6x3 + 7x2 - 3x2(2x + 1) = 6x3 - 6x3 + 7x2 - 3x2 = 4x2; bring down 7x2. 4x2 + 7x - 2x(2x + 1) = 4x2 - 4x2 + 7x - 2x = 5x bring down 13. 5x + 1 - 2(2x + 1) = 5x - 4x + 1 - 2 = x - 1 the reminderThus, (6x3 + 7x2 + 7x + 1)/(2x + 1) = 3x2 + 2x + 2 + (x - 1)/(2x + 1)and(12x3 + 14x2 + 14x + 2)/(4x + 2) = 3x2 + 2x + 2 + (2x - 2)/(4x + 2).
8x - 22 = 2x + 28x - 2x - 22 = 2x - 2x + 26x - 22 = 26x - 22 + 22 = 2+ 226x = 24x = 24/6 = 4
Integral of sqrt(2x) = integral of (2x)1/2 = √2/(3/2)*(x)3/2 + c = (2√2)/3*(x)3/2 + c where c is the constant of integration. Check: ( (2√2)/3*(2x)3/2 + c )' = (2√2)/3*(3/2)(x)(3/2)-1 + 0 = √2*(x)1/2 = √2x
3^(-2x + 2) = 81? log(3^(-2x + 2)) = log(81) (-2x+2)log(3) = log(81) -2x = log(81)/log(3) - 2 x = (-1/2)(log(81)/log(3)) + 1
2x - 1 = x + 15 Add 1 to both sides: 2x = x + 16 Subtract x from both sides: x = 16
It is an algebraic expression involving x. Of do you mean 'what is x if 2x - 9 equals 9?' 2x - 9 = 9 ⇒ 2x - 9 + 9 = 9 + 9 ⇒ 2x = 18 ⇒ 2x ÷ 2 = 18 ÷ 2 ⇒ x = 9
2x^2(3x - 2)(2x + 3)